Pengaruh Variasi Mengajar Guru dan Disiplin Belajar terhadap Hasil Belajar Siswa Kelas X pada Mata Pelajaran Ekonomi SMAN 1 Tulungagung Tahun Ajaran 2024/2025 - Gulo, Brian Hega Odien; Hastuti, Maria Agatha Sri Widyanti (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
In the current era of educational modernization, the success of the learning process is significantly influenced by the quality of teacher-student interaction and students' discipline in participating in academic activities. This study aims to determine: 1) the influence of teaching variation on student learning outcomes, 2) the influence of learning discipline on student learning outcomes, and 3) the simultaneous influence of teaching variation and learning discipline on student learning outcomes. This research employed a quantitative approach with a population of 77 Grade X students at SMA Negeri 1 Tulungagung, using a saturated sampling technique. Data collection was conducted using questionnaires for variables X1 and X2 and grade documentation for variable Y. The data analysis results show that: 1) partially, teaching variation does not have a significant effect on learning outcomes, with a t-value (1.016) < t-table (1.993) and a significance level of 0.313 > 0.05; 2) partially, learning discipline has a significant effect on learning outcomes, with a t-value (4.703) > t-table (1.992) and a significance level of 0.000 < 0.05; 3) simultaneously, teaching variation and learning discipline significantly affect student learning outcomes, with an F-value (13.356) > F-table (3.12) and a significance level of 0.000 < 0.05. The Adjusted R² value of 0.245 indicates that the studied variables influence learning outcomes by 24.5%, while the remaining 75.5% is influenced by other factors not examined in this research. It can be concluded that teaching variation does not have a significant effect on learning outcomes, whereas learning discipline does. Simultaneously, both variables together have a significant effect. These findings suggest that learning discipline plays a more dominant role in enhancing student learning outcomes compared to teaching variation.